Internal Influence Of Locus Of Control On Moral Disengagement Santri In West Java - Ulfiah Ulfiah; Tahrir Tahrir; Nisa Hermawati (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This paper examined the influence of internal locus of control on the moral disengagement of students at five Pesantren in West Java. The respondents in this study were 370 who were taken by simple random sampling. The questionnaire used for the daat collection that was made referring to the theory of internal locus of control and moral disengagement. The data analysis used a simple linear regression test and based on the results of statistical tests, it was known that the R value was -0.991 and the t value : -16,212 > t table: 1.65 and the sig.: 0.000 < :0.05, this meant that the internal locus of control had a negative and significant effect on moral disengagement, this study proved that the higher the internal locus of control score, the lower the moral disengagement behavior of students at five Islamic boarding schools in West Java.